Automatic mind maps generation for the Holy Quran / Akram M. Zeki, Hamed Issa and Shafiullah Wasiq - M. Zeki, Akram; Issa, Hamed; Wasiq, Shafiullah (Faculty of Information Management, 2022)
Millions of Muslims around the world welcome initiatives that improve how people read, recite, comprehend, and, memorize the wonderful lessons contained in the Holy Qur'an. The majority of the Holy Quran learners suffer from lack of quality in memorization understanding and connecting its topics. Therefore, the aim of this paper is to develop an algorithm that automatically generate the topics based on the mind map of a set of verses in the Holy Quran. By using this approach, we found the topics of all sets of verses based on the Topical Mushaf and Al-Duwayish mind map of Surat Al-Baqarah.